Sexual behaviours, awareness and perceptions towards voluntary medical male circumcision among students in Dr Kenneth Kaunda District, South Africa - Sam Mndzebele; Lebogang G. Matonyane (Southern African Journal of HIV Medicine, 2019)
Background: Voluntary Medical Male Circumcision (VMMC) is regarded as the most cost-effective intervention in reducing female-to-male transmission of HIV in countries where heterosexual transmission is the most prevalent mode of infection.